Influence of oil palm frond fiber loading on the morphological, mechanical, and acoustic properties of polyurethane composite foams - Budi Istana; Adriyan; Agus Mulyadi; Cici Maarasyid; Jeefferie Abd Razak (Mechanical Engineering for Society and Industry, 2026)
The development of sustainable acoustic materials is increasingly important for reducing environmental impact while maintaining functional performance. In this study, rigid polyurethane (PU) foams reinforced with oil palm frond (OPF) fibers were fabricated with fiber loadings of 0, 5, 10, and 15 wt% to investigate the structure–property–performance relationship. Morphological characterization by SEM revealed that increasing fiber content refined pore size from ~539–742 µm in neat PU to ~224–663 µm at 15 wt% OPF, with higher tortuosity and evidence of fiber pull-out. Mechanical testing showed that maximum compressive stress decreased systematically with fiber addition (0.19 N/mm² in neat PU to 0.10 N/mm² at 15 wt%), reflecting increased slurry viscosity, fiber agglomeration, and imperfect interfacial adhesion. Acoustic measurements demonstrated that 5 wt% OPF provided superior high-frequency absorption (α ≈ 0.95 at 2000 Hz), while 10 wt% OPF consistently underperformed due to pore blockage. At 15 wt%, absorption became more stable across mid-to-high frequencies (0.35–0.60), and when combined with a 10 mm air gap, the composites exhibited enhanced broadband performance, particularly between 400–1600 Hz. These results establish a clear link between fiber loading, cell morphology, compressive strength, and acoustic behavior. Low fiber contents are best suited for hybrid strength–acoustic applications, while higher loadings combined with cavity backing offer an eco-friendly route to broadband sound absorbers. The findings highlight OPF fibers as a promising renewable reinforcement for multifunctional PU foams in building and automotive insulation.